Association between bullous pemphigoid and psoriasis: Systematic review and meta‐analysis of case‐control studies. (23rd August 2018) - Phan, Kevin; Goyal, Sourabh; Murrell, Dedee F
Abstract: Several case reports and cohort studies have recently investigated the potential association between bullous pemphigoid (BP) and psoriasis. It has been speculated that chronic inflammation in the dermo‐epidermal junction can trigger exposure to antigens to autoreactive T cells, resulting in autoimmune blistering disease. However, the association described has been inconsistently reported amongst studies. We performed a systematic review and meta‐analysis to investigation this potential association. We identified four case–control studies for inclusion in the present meta‐analysis, with a total of 4035 bullous pemphigoid cases and 19 215 control cases. There was a significantly higher prevalence of psoriasis in BP compared to controls (2.6% vs 1.1%, OR 2.5, 95% CI 1.4–4.6). Subgroup analysis showed that this association remained significant in both males (3.0% vs 1.3%, OR 2.4, 95% CI 1.6–3.6) as well as females (1.9% vs 0.7%, OR 2.9, 95% CI 1.4–5.9). A significantly higher proportion of cases were reported in males (3.0% vs 1.9%, OR 1.75, 95% CI 1.1–2.7). This pooled analysis of existing case–control studies to date demonstrates a significant association between BP and psoriasis. We also showed that in contrast with the majority of autoimmune diseases which are predisposed in females, that the coexistence of BP and psoriasis appears to be predisposed in male patients.